Elastooptyka i metoda elementów skończonych w mechanice pękania : wybrane problemy - Niezgodziński, Tadeusz (Wydawnictwo Politechniki Łódzkiej, 2007)
The book contains results of numerical calculation and their comparison with experimental tests carried out on the specimens CT. Crack propagate until damage specimen was achieved. The angle between the direction of crack propagation and the direction of the artificial crack was measured. Author during numerical investigations compare Burzynski and Huber-MisesHencky hypothesis. The Burzynski hypothesis gives very good results for brittle materials which has different properties for tensile and compression it means that relationship between limit stress for compression Re to limit stress for tension Rm is greater than 1 (for example: epoxy resign, cast iron). Influence of relation R.!Rm on angle of crack propagation was carried out. The results of investigation gives information that for relation R.!Rm greater than 1,3 the value of angle of crack propagation is constant, and its value is about 76°. The experimental investigation is solved by photoelastic method. The numerical results were obtained using finite element method package ANSYS. The problem is solved by "element birth and death" method. Results of investigations of cracking of reinforced specimens are presented.
Photoelastic and fem method in the fracture mechanics
Red. serii : Wodziński, Piotr
Keywords: elastooptyka; metoda elementów skończonych; mechanika pęknięć; hipoteza Burzyńskiego; finite element method; mechanics of cracks